Impairment of attention network function in posterior circulation ischemia-evidence from the Attention Network Test - Li, Na; Li, Chuanjin; Xie, Xiaohui; Liu, Gang; Wang, Kai; Zhang, Wendong; Fan, Jin (Frontiers in Human Neuroscience, 2023)
Objective This study aimed to investigate the effect of posterior circulation ischemia (PCI) on attention network function and to determine whether PCI is holistic or selective attention network deficit and which attention network is affected. Methods Thirty-six PCI patients aged 30 to 75 were assessed using the Attention Network Test and the Mini-Mental State Examination (MMSE). There were no significant differences in age, sex, and education between PCI group and the control group (n = 32). All data were statistically analyzed by SPSS 23.0 software. Result There were no significant difference in the MMSE scores between the two groups. Compared with the control group, the PCI group had significantly shorter response time for alerting and orienting network. The executive control network response time was significantly longer in PCI group than in the control group. The overall mean response time was also significantly longer in PCI group than in normal control group. There was no significant difference in mean accuracy between the two groups. Conclusion The alerting, orienting, and executive control networks were significantly less efficient in PCI group than in the control group (P < 0.01). This indicates impaired attention network in PCI patients. Since transient nerve seizures caused by vertebrobasilar ischemia may precede posterior circulation stroke, early assessment of cognitive function in patients with PCI is particularly important, and ANT is an excellent tool for this assessment.